Interactions between the entomopathogenic fungus Beauveria bassiana and the Neotropical predator Eriopis connexa (Coleoptera: Coccinellidae): Implications in biological control of pest - Scorsetti, Ana Clara (2017)
Aphids (Hemiptera: Aphididae) are serious pests of crops causing direct damage by feeding and indirect by the transmission of plant viruses. The use of conventional insecticides for controlling aphids has caused different problems and insecticide resistance. Accordingly, there is more interest in alternative control methods such as biological control by natural enemies for sustainable agricultural management. Among biological control agents, entomopathogenic fungi are one of the most significant microbial pathogens of insects. Also, Coccinellidae, as a major group, is a serious natural enemy. Both larval and adult stages of Coccinellidae feed on different soft-body pests, such as aphids. Eriopis connexa (Germar) (Coleoptera: Coccinellidae) is a common species in agroecosystems of the Neotropical region where it is considered to be a potential control agent. Pathogens and arthropod natural enemies may contribute to the control of phytophagous pests; however, it is important to assess potential interactions within biological control agents that share hosts (intraguild interaction) to evaluate their combined use for pest control. Therefore, the aim of this study was to evaluate the compatibility and interaction (lethal and sublethal effects) between E. connexa and the entomopathogenic fungus Beauveria bassiana (Bals.-Criv.) Vuill. (Ascomycota: Hypocreales). Both are important biological control agents of aphids. The pathogenicity of B. bassiana against larvae, pupae and adults of the predator E. connexa was evaluated, and results showed, that B. bassiana infected the coleopteran. On the other hand, interaction between B. bassiana and the predator was evaluated through infected-prey. The effects of fungus on larvae survival were significantly different when we analyzed the accumulated survival (from first larval instar to adulthood). The daily fecundity was significantly reduced at five days compared to control group. By contrast, no significant differences were observed between the five oviposition days in the rate of hatched eggs. This study shows that despite having received a single dose of the fungus in its life cycle, the population parameters of the predator E. connexa are affected. More studies would be necessary to help identify interactions between microbes and natural enemies to increase and enhance opportunities and further develop biological pest control programs.